2023
DOI: 10.1007/jhep03(2023)189
|View full text |Cite
|
Sign up to set email alerts
|

Medium-induced radiation with vacuum propagation in the pre-hydrodynamics phase

Abstract: The recent discovery of the potential of jet quenching observables to constrain the initial stages after a heavy-ion collision makes imperative to have a better understanding of the process of medium-induced radiation before the formation of the quark-gluon plasma (QGP) and its impact on observables at high-pT. In this work, we generalize the BDMPS-Z framework for medium-induced radiation to account for additional emissions occurring before the creation of the QGP. For simplicity, we assume that during the pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 74 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…with transverse momenta 𝑞 ⊥,𝑖 with 𝑖 = 𝑦 or 𝑧. It has been pointed out recently that pre-equilibrium dynamics may have sizable effects on heavy-quark diffusion and jet quenching [42,[47][48][49][50][51][52]. More specifically, the transport coefficients 𝜅 and q have been recently computed during the Glasma phase [41,42,48,50,[53][54][55] using force-force correlations or, alternatively, Wong's equations in classical-statistical simulations.…”
Section: Pos(hardprobes2023)008mentioning
confidence: 99%
“…with transverse momenta 𝑞 ⊥,𝑖 with 𝑖 = 𝑦 or 𝑧. It has been pointed out recently that pre-equilibrium dynamics may have sizable effects on heavy-quark diffusion and jet quenching [42,[47][48][49][50][51][52]. More specifically, the transport coefficients 𝜅 and q have been recently computed during the Glasma phase [41,42,48,50,[53][54][55] using force-force correlations or, alternatively, Wong's equations in classical-statistical simulations.…”
Section: Pos(hardprobes2023)008mentioning
confidence: 99%
“…However, most of jet quenching phenomenological studies typically neglect any quenching effects prior to the hydrodynamization phase. Recent studies have shown that certain energy loss observables are indeed sensitive to these early stages [44][45][46]. Nevertheless a comprehensive understanding of the impact of these initial stages on jet quenching observables in heavy-ion collisions is still lacking.…”
Section: Pos(hardprobes2023)013mentioning
confidence: 99%
“…The Glasma fields are obtained in the proper time expansion and the transport of the hard probes is treated using the Fokker-Planck equations adapted to the Glasma. Complementary, it was shown that the initial stage, implemented in different frameworks, has an effect on jet quenching [38,39]. Even though these approaches vary with respect to the approximations which are used, they all converge to the same key result: the Glasma phase has a considerable effect on the transport of hard probes.…”
Section: Introductionmentioning
confidence: 99%